A conceptual learner discipline management model for secondary schools in Mauritius - Belle Louis Jinot; Van Niekerk Eldridge Johannes (Institute of Advanced Engineering and Science, 2021)
Learner discipline management is a major but challenging function of school leadership. Adolescents of the 21st century are complex in nature, and school stakeholders are having much difficulty to handle the problem of indiscipline in secondary schools. This paper aims at providing a conceptual model framework for learner discipline management. This model is the result of an empirical investigation conducted in four secondary schools. Focus group discussion and individual interviews were carried out with 80 participants, including 24 teachers, 24 learners, 24 parents, four school principals, and four school superintendents. The non-participant observation was also conducted in the four schools. Based on the conceptual, theoretical and empirical literature on positive, proactive, preventive and restorative discipline, the researcher proposed the model that considers all the research- and evidence-based strategies that are combined with the current effective measures prescribed by the Ministry of Education, Science and Technology of Mauritius. The model is framed within the context of the Nine Year Continuous Basic Education reform that requires a shift in the conception of discipline from the punitive or reactive approach to the positive approach. This paper formulates a conceptual model framework to implement in an attempt to prevent, reverse and restore discipline among learners in secondary schools.